Pengaruh Motivasi Dan Kompetensi Terhadap Kinerja Pegawai Pada Kantor Pengawasan Dan Pelayanan Bea Dan Cukai Tipe Madya Pabean Tanjung Emas - Yudha Khoirunnizar; Sutopo Sutopo (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2022)
This research is motivated by the performance achievements of the employees of the Tanjung Emas Middle Type Customs and Excise Office of Supervision and Service Office which have not been achieved. The purpose of this study was to analyze the influence of Motivation (X1) and Competence (X2) on Employee Performance (Y) in the Customs and Excise Supervision and Service Office of the Middle Type of Customs Tanjung Emas. Descriptive analysis in this study uses the index number method. Determining the number of samples was calculated based on the slovin formula and obtained a sample of 71 employees from a total population of 248 employees. The sampling method uses simple random sampling technique. The results of the analysis show that motivation has no significant positive effect on employee performance. This is indicated by the calculated t value which is smaller than t table, namely 0.481 <1.667 (df = 68), with a significance value of 0.632 which is greater than α = 0.05. Motivation (β1) is positive at 0.042 which means that there is no effect of motivation on performance (not significant). The results of the analysis show that competence has a significant positive effect on employee performance. This is indicated by the calculated t value that is greater than t table, namely 8.028 > 1.667 (df = 68), with a significance value of 0.000 which is smaller than α = 0.05. Competence (β2) has a positive sign of 0.705 which means that the higher the competency, the higher the employee's performance (significant).